A STUDY OF THE IMAGE OF TULIP SYMPHONY - A DEFINING INGREDIENT IN THE DEVELOPMENT OF THE URBAN BRAND OF PITESTI - Mihaela, ASANDEI; Elena, ENACHE (Strategii Manageriale)
The city is a fundamental element of the identity of contemporary society, fulfilling in each urban community complex functions that depend on the needs, interests and aspirations of the people and of the political and economic system. The urban identity of Pitesti is defined by a set of features with certain significance for each inhabitant of the city. The Tulip Symphony is a symbol that has been created, developed and promoted during the past four decades by the urban community. The present study aims to study how residents of Pitesti perceive the urban product named the Tulip Symphony is and present the conclusions of a statistical survey conducted during the 37th edition of the event.